Development of Data Processing Software for NBI Spectroscopic Analysis System*supported by National Natural Science Foundation of China (No. 11075183), the Chinese Academy of Sciences Knowledge Innovation. (April 2015) - Zhang, Xiaodan; Hu, Chundong; Sheng, Peng; Zhao, Yuanzhe; Wu, Deyun; Cui, Qinglong
Abstract A set of data processing software is presented in this paper for processing NBI spectroscopic data. For better and more scientific managment and querying these data, they are managed uniformly by the NBI data server. The data processing software offers the functions of uploading beam spectral original and analytic data to the data server manually and automatically, querying and downloading all the NBI data, as well as dealing with local LZO data. The set software is composed of a server program and a client program. The server software is programmed in C/C++ under a CentOS development environment. The client software is developed under a VC 6.0 platform, which offers convenient operational human interfaces. The network communications between the server and the client are based on TCP. With the help of this set software, the NBI spectroscopic analysis system realizes the unattended automatic operation, and the clear interface also makes it much more convenient to offer beam intensity distribution data and beam power data to operators for operation decision-making.